2017
DOI: 10.1038/s41598-017-00601-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term electrical stimulation at ear and electro-acupuncture at ST36-ST37 attenuated COX-2 in the CA1 of hippocampus in kainic acid-induced epileptic seizure rats

Abstract: Seizures produce brain inflammation, which in turn enhances neuronal excitability. Therefore, anti-inflammation has become a therapeutic strategy for antiepileptic treatment. Cycloxygenase-2 (COX-2) plays a critical role in postseizure brain inflammation and neuronal hyperexcitability. Our previous studies have shown that both electrical stimulation (ES) at the ear and electro-acupuncture (EA) at the Zusanli and Shangjuxu acupoints (ST36–ST37) for 6 weeks can reduce mossy fiber sprouting, spike population, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…e Zusanli acupoint (ST36) is 3-4 mm below the knee joint and 1-2 mm outside the tibia crest. Shangjuxu acupoint (ST37) is located 7-8 mm below the knee joint and 1-2 mm outside the tibia crest [35]. e rat was fixed in a self-made fixator.…”
Section: Electroacupuncture and Drugs Treatmentmentioning
confidence: 99%
“…e Zusanli acupoint (ST36) is 3-4 mm below the knee joint and 1-2 mm outside the tibia crest. Shangjuxu acupoint (ST37) is located 7-8 mm below the knee joint and 1-2 mm outside the tibia crest [35]. e rat was fixed in a self-made fixator.…”
Section: Electroacupuncture and Drugs Treatmentmentioning
confidence: 99%
“…Accordingly, these medicines have severe side effects on cognition and memory [ 1 , 2 ]. Epilepsy is the result of an imbalance between excitatory and inhibitory function and can be induced in animal models by overactivation of excitatory neurotransmitter receptors through a kainic acid (KA) injection, which is utilized to initiate epileptic seizures [ 3 ]. Another method to induce epileptic seizures involves blocking the inhibitory GABA A receptors, and this can be performed using pilocarpine [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture has been used in Asia for thousands of years to treat diseases. A number of studies have indicated that electroacupuncture (EA) can be used to treat stroke-induced dementia [ 16 ], epilepsy [ 3 ], body weight control [ 17 ], Parkinson's disease [ 18 ], depression [ 19 ], and pain [ 20 , 21 ]. Initially, scientists determined that acupuncture treatment worked through the release of endogenous opiates [ 22 ], serotonin [ 23 ], and adenosine [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 is usually present at low levels under normal conditions, but is rapidly and robustly induced by stimuli including infection, injury and pain to initiate pro-inflammatory processes that could facilitate and maintain the disease states 3 5 . As a major COX-2 product within the brain, PGE 2 has been widely thought to promote the neuronal inflammation and degeneration in many neurological diseases such as ischemic stroke 6 , 7 , epilepsy 8 10 , neurodegenerative diseases 11 13 , brain tumor 14 , 15 , inflammatory pain 16 , etc. PGE 2 can bind and activate four G protein-coupled receptors (GPCRs): EP1, EP2, EP3 and EP4.…”
Section: Introductionmentioning
confidence: 99%